2020
DOI: 10.3390/ani10112155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Body Behaviors and Facial Expressions Associated with Induced Orthopedic Pain in Four Equine Pain Scales

Abstract: Equine orthopedic pain scales are targeted towards horses with moderate to severe orthopedic pain. Improved assessment of pain behavior and pain-related facial expressions at rest may refine orthopedic pain detection for mild lameness grades. Therefore, this study explored pain-related behaviors and facial expressions and sought to identify frequently occurring combinations. Orthopedic pain was induced by intra-articular LPS in eight horses, and objective movement asymmetry analyses were performed before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…Some of the most widely used horse pain scales involve social interaction between the observer and the horse, that is, touching, feeding the horse or palpating the sore area [18]. A recent study [79] showed that these types of scales generally perform well, but if the pain is evaluated using one of these scales by direct observation, video recordings for CV/ML purposes should be made immediately before the direct pain scoring. It is also important to test the system in another population of horses, to prevent reliance on spurious correlations.…”
Section: Requirements On Video Recordings For Use In Computer Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most widely used horse pain scales involve social interaction between the observer and the horse, that is, touching, feeding the horse or palpating the sore area [18]. A recent study [79] showed that these types of scales generally perform well, but if the pain is evaluated using one of these scales by direct observation, video recordings for CV/ML purposes should be made immediately before the direct pain scoring. It is also important to test the system in another population of horses, to prevent reliance on spurious correlations.…”
Section: Requirements On Video Recordings For Use In Computer Visionmentioning
confidence: 99%
“…To determine whether a pain scale can deliver ground truth, it is necessary to know the performance parameters of the pain scale used for the actual population tested during the actual conditions. Surprisingly, few pain scales are adequately validated in this regard [54,79] since sensitivity and specificity can only be measured against ground truth. In horses, a number of pain assessment scales based on facial expressions have been presented recently.…”
Section: Will a Pain Scale Deliver Ground Truth?mentioning
confidence: 99%
See 1 more Smart Citation
“…A search of veterinary, animal science, and equine behavior science literature (English language, from mid 20th century to the present) was undertaken to identify research reports and review articles or book chapters describing behaviors associated with physical discomfort in horses. Forty-five such sources [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were reviewed to confirm agreement with our identified behaviors, as well as to identify any behavioral elements or sequences reported to reflect physical discomfort in horses that had not been identified in our clinical observations.…”
Section: Background Detailsmentioning
confidence: 99%
“…Observing the natural behavior of horses in their home environment is helpful as the stress and excitement of being in unfamiliar surroundings will cause some horses to override signs of pain and discomfort. Behavioral assessment is an important part of the overall examination to take note of [22]. Careful attention should be paid to the horse's stance, facial expressions, and how the horse interacts with its surroundings and humans.…”
Section: Observationmentioning
confidence: 99%